Re-Discovering Christian Eco-theological Ethics (Hekima Review, 2010)
There is a concerted effort to avert the impending ecological disaster. Religions try to remedy the ‘spiritual inadequacy’ to face the ecological crisis by rediscovering their resources. Christianity, with the theology of ‘dominating earth’, is often accused of having been responsible for the present crisis. It may be true that certain emphases in the Christian tradition did not facilitate a reverential attitude to nature. But, it will be unjust to attribute to Christianity the sole responsibility. The main reason for the present ecological crisis seems to be the neo-liberalist ideology that promotes competition based market, unlimited profit and consumerism. A critical reading of the Bible demands that we develop a reverential attitude to nature. Other religious traditions like Hinduism can help us re-discover further our own eco-theology. Ecological crisis is basically an ethical issue, an issue of justice and demands a radical change in the present dominant style. Eco-theological ethics gives the possibility of interreligious dialogue and collaborative action.